2014
DOI: 10.1038/bjc.2014.170
|View full text |Cite
|
Sign up to set email alerts
|

Molecular staging of lymph node-negative colon carcinomas by one-step nucleic acid amplification (OSNA) results in upstaging of a quarter of patients in a prospective, European, multicentre study

Abstract: Background:Current histopathological staging procedures in colon carcinomas depend on midline division of the lymph nodes with one section of haematoxylin & eosin (H&E) staining only. By this method, tumour deposits outside this transection line may be missed and could lead to understaging of a high-risk group of stage UICC II cases, which recurs in ∼20% of cases. A new diagnostic semiautomated system, one-step nucleic acid amplification (OSNA), detects cytokeratin (CK) 19 mRNA in lymph node metastases and ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 26 publications
1
50
1
Order By: Relevance
“…Other studies also showed that pN0 CRC patients were up-staged by OSNA test in 15.3-28.8%. 13,15,24,25 It is suggested that difference of detection rate depends on sampling of LN volume and number. 24 Notably Rakislova et al 24 reported that 20.8% pN0 cases were OSNA-positive by the pooling method which would be helpful as compared to time consuming and expensive individual analysis of LNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also showed that pN0 CRC patients were up-staged by OSNA test in 15.3-28.8%. 13,15,24,25 It is suggested that difference of detection rate depends on sampling of LN volume and number. 24 Notably Rakislova et al 24 reported that 20.8% pN0 cases were OSNA-positive by the pooling method which would be helpful as compared to time consuming and expensive individual analysis of LNs.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have further demonstrated the high sensitivity of OSNA in detecting LN metastasis of breast, gastric, lung, and colorectal cancers. [9][10][11][12][13][14][15][16] Our own previous prospective, multicenter studies conducted in Japan demonstrated the usefulness of the OSNA assay as a complementary tool for diagnosing LN metastasis and CRC staging. 17,18 The later study revealed that 17.6% (13/74) of patients with histologically node-negative stage II CRC were nodal positive by the OSNA assay.…”
mentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer diagnosed in both men and women [1]. The lifetime risk of developing CRC is about 1 in 21 (4.7%) for men and 1 in 23 (4.4%) for women.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime risk of developing CRC is about 1 in 21 (4.7%) for men and 1 in 23 (4.4%) for women. Many factors increase the risk including: obesity, diet high in red meat (such as beef, pork, lamb, or liver) and processed meat, smoking, heavy alcohol use, history of inflammatory bowel disease, family history of CRC or adenomatous polyps and diabetes mellitus [1]. Although colonoscopic screening for CRC is the most reliable tool; its difficulties and costs have hampered its wide application.…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer and colorectal cancer, CK19 mRNA levels were shown to be useful for identifying lymph nodes that harbored metastatic cells. 23,24 While the expression of CK19 in Station 8 lymph nodes implies the presence of pancreatic cancer cells in these nodes, there was no difference in CK19 mRNA levels between patients with recurrent versus non-recurrent disease. By contrast, among the miRNAs examined in the current study, high levels of miRNA-10b, but not the other miRNAs currently investigated, were significantly increased in patients who developed cancer recurrence.…”
Section: Discussionmentioning
confidence: 93%